Audience Cognition Through Elaboration Likelihood Model Process: Instagram Content of Indonesian Health Ministry on Stunting Phenomenon - Hapsari, Richiana; Yoma Bagus Pamungkas, (INJECT (Interdisciplinary Journal of Communication), 2024)
This study assesses the impact of the Instagram campaign “25.000 Penentu Generasi Penerus” on the audience's cognitive response to Indonesia’s stunting education efforts. Using an explanatory quantitative method, data was collected via online questionnaires and analyzed using Variance-Based Structural Equation Modeling (VB-SEM) and Generalized Structured Component Analysis (GSCA). The findings suggest that Instagram content and perceived persuasiveness have a direct, positive, and significant influence on the cognitive responses of the @kemenkes_ri Instagram content viewers, with the effect being moderate to high. However, perceived persuasiveness significantly influences audience behavior change when it acts as a mediator. Thus, it is essential for the Ministry of Health of the Republic of Indonesia (Kemenkes RI) to maintain high-quality messaging in stunting education content and to enhance the selection of highly credible figures as sources in the content.